ChemInform Abstract: Cu(II) Catalyzed Chemoselective Oxidative Transformation of Thiourea to Thioamidoguanidine/2‐Aminobenzothiazole. Issue 21 (2nd May 2013) - Sahoo, Santosh K.; Khatun, Nilufa; Gogoi, Anupal; Deb, Arghya; Patel, Bhismar K.
Abstract Unsymmetrical thioureas, prepared in situ from isothiocyanates (I) and secondary amines (II), are oxidized by Cu(II) to the corresponding disulfide intermediates, which suffer an imine‐disulfide rearrangement to give thioamidoguanidines (III).